Pelatihan Pemanfaatan ChatGPT dan Scite.ai untuk Meningkatkan Kualitas Penulisan Artikel Pengabdian - Hunaepi Hunaepi; Sulami Sibua; Muhammad Asy’ari; Muhammad Ikhsan; Dadang Warta Candra Wira Kesuma; Aminullah Aminullah; Saiful Prayogi; Nova Kurnia; Baiq Mirawati; Irham Azmi; Rospin Hidayati; Maya Afrilyana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service activity aims to improve the competence of lecturers at the Faculty of Culture, Management, and Business, Mandalika University of Education, in writing quality community service articles through the use of artificial intelligence technology, specifically ChatGPT and Scite.ai. The method used was an interactive workshop based on direct practice, equipped with a pre-test, delivery of theoretical materials, practice using AI, post-test, and reflection sessions. The analysis results showed a significant increase in post-test scores compared to the pre-test, with the majority of participants' N-gain being in the medium to high category. Participants were also able to produce draft community service articles with good to very good quality categories based on the assessment rubric. The level of participant satisfaction with the materials, methods, and implementation of the workshop was in the high category, indicating the success of the training approach used. This activity also contributed to the achievement of the SDGs, especially the goals of Quality Education (SDG 4), Innovation and Infrastructure (SDG 9), and Partnership (SDG 17). This training can be replicated as a model for increasing lecturer capacity in the context of digital transformation of higher education.